2018
DOI: 10.1186/s13071-018-2887-4
|View full text |Cite
|
Sign up to set email alerts
|

Culex flavivirus infection in a Culex pipiens mosquito colony and its effects on vector competence for Rift Valley fever phlebovirus

Abstract: BackgroundRift Valley fever is a mosquito-borne zoonotic disease that affects domestic ruminants and humans. Culex flavivirus is an insect-specific flavivirus that naturally exists in field mosquito populations. The influence of Culex flavivirus on Rift Valley fever phlebovirus (RVFV) vector competence of Culex pipiens has not been investigated.MethodsCulex flavivirus infection in a Cx. pipiens colony was studied by Culex flavivirus oral feeding and intrathoracical inoculation. Similarly, vector competence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…In vivo studies showed a delay of dissemination from the midgut by 3 days 2015 [ 31 ] Hall-Mendelin et al PCV No Yes WNV Significantly lower infection rate in PCV-infected Cx. Annulirostris orally exposed to WNV 2016 [ 98 ] Talavera et al CxFV No Yes RFV No effect 2018 [ 94 ] Schultz et al CFAV, PCLV Yes No ZIKV, DENV & LACV 90% reduction of ZIKV & DENV growth. Complete inhibition of LACV at MOI 0.1 2018 [ 104 ] …”
Section: Vector Competence Studiesmentioning
confidence: 99%
“…In vivo studies showed a delay of dissemination from the midgut by 3 days 2015 [ 31 ] Hall-Mendelin et al PCV No Yes WNV Significantly lower infection rate in PCV-infected Cx. Annulirostris orally exposed to WNV 2016 [ 98 ] Talavera et al CxFV No Yes RFV No effect 2018 [ 94 ] Schultz et al CFAV, PCLV Yes No ZIKV, DENV & LACV 90% reduction of ZIKV & DENV growth. Complete inhibition of LACV at MOI 0.1 2018 [ 104 ] …”
Section: Vector Competence Studiesmentioning
confidence: 99%
“…Part of the uncovered microbiome is the insect-specific viruses (ISVs), viruses restricted to arthropods that are unable to replicate in vertebrate cells [27]. Insect-specific viruses are highly prevalent in wild mosquito populations [25,[28][29][30][31] and have been reported to suppress [32][33][34][35][36], enhance [37,38], or have no effect [39] on replication of medically important arboviruses, potentially affecting vector competence [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…quinquefasciatus co-infected with CxFV Izabal [60] and CxFV did not impact RVFV infection in Cx. pipiens mosquitoes [61]. Co-infection studies using cell-fusing agent virus (CFAV, Flavivirus) and dengue virus (DENV) in Aag2 cells shows mutual interaction through activation of Ribonuclease K (AeRNASEK) expression [14], whereas in Ae.…”
Section: Discussionmentioning
confidence: 99%